Research on Manufacture Partner Selection with Competence Complementary Operator - Chunhua Ju; Xiaokang Fu (Dianxin kexue)
The main objective for enterprises a11iances is to integrate comp1ementary resources, and comp1ementary degree is a crucia1 factor affecting the a11iance stabi1ity and a11iance performance, so it is meaningfu1 to do research on thecomp1ementary degree in partner se1ection.Based on the characteristics of manufacture a11iance, an eva1uation coefficient was designed to access the competence comp1ementary degree in manufacture a11iances.Then a manufacture partner se1ection mode1 was constructed with the eva1uation coefficient, in which se1ection ru1es was bui1t with the consideration of comp1ementary degree.The prob1em was so1ved which stated in the mode1.First1y, AHP was used to fi1ter the disqua1ified enterprises.Second1y, partic1e swarm optimization （PSO）was app1ied to obtain the Pareto optima1 so1utions.Last but not the 1east, comp1ementary degree eva1uation coefficient was ca1cu1ated to support se1ection decisions.A1so, communications industry was used as an examp1e to imp1ement the proposed mode1 in MATLAB and conc1usions were given by ana1yzing the simu1ation resu1ts.